Konservasi Kesenian Goong Gede pada Masyarakat Desa Citorek, Lebak-Banten - Wisnu Wirandi (PANTUN, 2017)
Goong Gede art communicates the old history of the ancestors of the people. The event is the belief manifestation toward the relationship from the past until the present and the future. The belief forms the basis of the people’s expressions to ward the phenomena in the socio cultural surrounding by obeying the customary rules in Citorek village either related to the agricultural or daily life maters. The values convinced by the people become the media of the sociocultural and the environment conservation of the society. The conservation of Goong Gede is the manifestation of identity protection of surrounding culture from the e?ect of globalization. This study is aimed to analyze and interpret the myth of Goong Gede as the identity of Citorek People in Lebak Banten.Keywords: Conservation, Goong Gede, identity, myth